COLLABORATIVE VIDEO LOGS: VIRTUAL COMMUNITIES OF PRACTICE AND ALIVENESS IN THE MUSIC CLASSROOM - Cayari, Christopher (AoIR Selected Papers of Internet Research, 2019)
A vlog or videoblog is a series of videos that feature someone speaking to the camera to present entertainment, reflection, opinion, or education. Collaborative vlogs (CVLs) involve multiple people taking joint ownership of a vlog through asynchronous interaction, discussion, and expression. This paper explores how online video helped create communities of practice both within the classroom and beyond through developing connections with each other that extended their interactions from the classroom to the Internet. Additionally, they creatively explored new ways to express themselves, developed their identities, and discussed pertinent topics regarding music, technology, and education. To explore the sociological vectors of culture and identity, I adapted a framework of aliveness within communities of practice developed by Wenger, McDermott, and Snyder (2002) to analyze seven semesters of student reflections on CVL projects in music courses that serviced music education majors, elementary education majors, and students from a variety of majors. Through CVLs, students have explored mediated musical practices and shared their lives and experiences in ways that classmates and instructors do not get to see when limited to the classroom. Students and vloggers alike deal with issues of trust within our digital society, and by critically analyzing how the participants in this study developed relationships with each other and me as their instructor, we can better understand how to move forward in the classroom and through social media, video broadcasting sites, and blogging. While the participants in this study were music students, CVLs can be applied to any discipline.